L.D. Landau. - Landau, L. D. (Lev Davidovich), 1908-1968 (Commonwealth and international library. Selected readings in physics., 1969)
Men of Physics: L.D. Landau, Volume 2: Thermodynamics, Plasma Physics and Quantum Mechanics is dedicated to L.D. Landau's contributions in the fields of thermodynamics, plasma physics, and quantum mechanics. Landau's theory of second-order phase transitions is discussed, along with his contributions to nuclear physics, astrophysics, cosmic ray physics, and quantum field theory. This volume is comprised of 15 chapters and begins with a discussion on Landau's theory of second-order phase transitions, which includes his assumption that all thermodynamic functions would allow regular series expa.